2019
DOI: 10.1039/c8na00059j
|View full text |Cite|
|
Sign up to set email alerts
|

Noble metal supported hexagonal boron nitride for the oxygen reduction reaction: a DFT study

Abstract: Discovering active, stable and cost-effective catalysts for the oxygen reduction reaction (ORR) is of utmost interest for commercialization of fuel cells. Scarce and expensive noble metals such as Pt and Pd are the state-of-the-art active ORR catalysts but suffer from low stability against CO poisoning. Hexagonal boron nitride (h-BN) is a particularly attractive material due to its low cost and stability; however, it suffers from intrinsic low activity toward the ORR in the pristine form as a result of its inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 56 publications
2
27
0
Order By: Relevance
“…Symbols ●, ▲, ♦, and ■ indicate Ag, Cu, Pd, and Pt supports, respectively. Reproduced with permission . Copyright 2019, The Royal Society of Chemistry.…”
Section: Energy‐related Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Symbols ●, ▲, ♦, and ■ indicate Ag, Cu, Pd, and Pt supports, respectively. Reproduced with permission . Copyright 2019, The Royal Society of Chemistry.…”
Section: Energy‐related Applicationsmentioning
confidence: 99%
“…In addition, depending on the structure of these materials, vacancy engineering can be used to fine‐tune or tailor properties according to the specific needs of the application. For materials featuring X a and X a Y b structures, vacancy engineering is primarily used to adjust the energy band structure and regulate the electronic environment around vacancies 13a,d,44. In M a X b and M a X b Y c structures, X and Y vacancies can be used to regulate the adsorption energy of reaction intermediates, and to optimize ion diffusion paths, which renders each vacancy a catalytic active site 28,42e,45.…”
Section: Energy‐related Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergence of two-dimensional (2D) materials over recent years has offered a number of promising candidates for improving the electrocatalysis of ORR/OER due to their high specific surface area and high surface density of active catalytic sites. Some materials of interest to Li-O 2 batteries are nitrogen-doped graphene 26 , hexagonal boron nitride (h-BN) on Ni surfaces 14,27 , and molybdenum carbide (Mo 2 C) 28 . Layered transition metal-carbide and metalnitrite MXenes with the general formula of M n+1 X n , with M being a transition metal and X = {C, N}, are highly stable 2D materials containing 2n + 1 layers of atoms 29 (see Supplementary Fig.…”
mentioning
confidence: 99%
“…This demonstrated the inertness of pure BN and verified that the interaction between BN and the Au substrate is a major influencing factor, which is consistent with Uosaki's experiment and previous theoretical results. [ 187,188,192 ] A similar work has been conducted by Banks and co‐workers [ 237 ] For C‐based substrates, it was found that the ORR catalytic activity of 2D h‐BN was highly dependent on the C material and cover/mass ratio. The h‐BN modified screen‐printed graphite electrode (SPE) showed a better electrochemical response than the GC‐ and B‐doped diamond electrodes.…”
Section: Boron Nitride For Electrochemical Catalysismentioning
confidence: 73%